Effect of high energy milling on microstructure and mechanical properties of Al2O3-10 wt% Co composites consolidated by spark plasma sintering (SPS). Issue 1 (1st January 2021) - Raimundo, Rafael A.; Santos, Kaio V.A.; Lourenço, Cleber S.; Costa, Franciné A.; Morales, Marco A.; Macedo, Daniel A.; Silva, Angelus G.P.; Gomes, Uílame U.
Abstract: Al2 O3 -10 wt% Co composites were prepared by high energy milling in the presence of ethyl alcohol and with subsequent spark plasma sintering (SPS). The powders milled for 5 and 30 h were sintered by SPS at 1350 °C for 5 min. The effect of milling time on the sinterability and mechanical properties was studied. The morphology and structure of milled powders were investigated by scanning electron microscopy, dynamic light scattering and X-ray diffraction. The Co phase forms plate-like particles of different sizes, while finely fragmented Al2 O3 particles are incorporated in the Co phase, forming composite particles. The average size of the composite particles decreases with increasing milling time, achieving 1.33 μm after 30 h. Crystallite size and micro-strain are inversely proportional. Overall, all the samples display homogeneous microstructures, high density (85.29–91.60%) and microhardness in the range 11.41–14.37 GPa. Highlights: Al2 O3 -10 wt% Co composites prepared by HEM. The shape and size of the particles were modified during HEM. Spark Plasma Sintering of Al2 O3 -10 wt% Co at 1350 °C. Relative density of 91.60% and microhardness of 14.37 GPa for samples milled for 30 h.